The Constitution and Public Administration - Shupitskaya, Aksana (Public Governance, Administration and Finances Law Review, 2018)
The article is devoted to the analysis of the ratio of public administration and the Constitution. At the same time, under public administration, the author understands the activities of state bodies and their officials to transform social relations for the benefit of society and the state. And under the Constitution – the Basic Law (or the sources of law) of the state and society, containing the system of constitutional principles and norms and ensuring the achievement and preservation of constitutional values. The main task of the author is to confirm that the Constitution is the basis and at the same time the framework of public administration, and the constitutional values are the purpose of its implementation.